Bargaining and gendered authority: a framework to understand household decision-making about childhood vaccines in the Philippines - Wachinger, Jonas; Reñosa, Mark Donald; Endoma, Vivienne; Aligato, Mila F.; Landicho-Guevarra, Jhoys; Landicho, Jeniffer; Bravo, Thea Andrea; McMahon-Rössle, Shannon A. (BMJ global health, 2022)
Introduction Targeted vaccination promotion efforts aimed at building vaccine confidence require an in-depth understanding of how and by whom decisions about vaccinating children are made. While several studies have highlighted how parents interact with other stakeholders when discussing childhood vaccination, less is known about the way in which vaccination uptake is negotiated within households. - Methods We conducted 44 in-depth interviews with caregivers of children under five in the Philippines who had delayed or refused vaccination. Interviews were conducted between August 2020 and March 2021 and were audio-recorded, transcribed verbatim and translated into English. Notions of intra-household vaccination bargaining emerged early during systematic debriefings and were probed more pointedly throughout data collection. - Results Parents as well as paternal and maternal families proved to be dominant stakeholders in intra-household bargaining for childhood vaccination. Although bargaining among these stakeholders was based on engrained, gender-based power imbalances, disadvantaged stakeholders could draw on a range of interrelated sources of bargaining power to nevertheless shape decision-making. Sources of bargaining power included, in descending order of their relevance for vaccination, (1) physical presence at the household (at the time of vaccination decision-making), (2) interest in the topic of vaccination and conviction of one’s own position, (3) previous vaccination and caregiving experience, and (4) access to household resources (including finances). The degree to which each household member could draw on these sources of bargaining power varied considerably over time and across households. - Conclusion Our findings highlight how bargaining due to intra-household disagreement coins decisions regarding childhood vaccination. Considering the risks for public health associated with vaccine hesitancy globally, we advocate for acknowledging intra-household dynamics in research and practice, such as by purposefully targeting household members with decision-making capacity in vaccination promotion efforts, aligning promotion efforts with available bargaining capacity or further empowering those convinced of vaccination.
Gesehen am 17.01.2023